Synchronization of Interphase Events Depends neither on Mitosis nor on cdk1 - Laronne, Ayelet (The American Society for Cell Biology, 2003)
Human HT2-19 cells with a conditional cdk1 mutation stop dividing upon cdk1 inactivation and undergo multiple rounds of endoreplication. We show herein that major cell cycle events remain synchronized in these endoreplicating cells. DNA replication alternates with gap phases and cell cycle-specific cyclin E expression is maintained. Centrosomes duplicate in synchrony with chromosome replication, giving rise to polyploid cells with multiple centrosomes. Centrosome migration, a typical prophase event, also takes place in endoreplicating cells. The timing of these events is unaffected by cdk1 inactivation compared with normally dividing cells. Nuclear lamina breakdown, in contrast, previously shown to be dependent on cdk1, does not take place in endoreplicating HT2-19 cells. Moreover, breakdown of all other major components of the nuclear lamina, like the inner nuclear membrane proteins and nuclear pore complexes, seems also to depend on cdk1. Interestingly, the APC/C ubiquitin ligase is activated in these endoreplicating cells by fzr but not by fzy. The oscillations of interphase events are thus independent of cdk1 and of mitosis but may depend on APC/C(fzr) activity.